The Use of Rhetorical Arts in Wisdom Poetry and Its Impact on Societies - Abdullah, Prof. Dr. Uday Khalid Mahmoud Abdullah Al-Badrani; Al-Jumaili, Prof. Dr. Shamel Ubaid Dar’ Mushwah Al-Jumaili (Sulaimani Journal for Humanities, 2026)
The study is based on tracing the rhetorical arts in wisdom poetry across the Arab ages, and examining the nature of their use on the one hand, and the possibility of their influence on Arab societies on the other hand; based on the language techniques that impose themselves on the connotations of the context, giving it what the lexical meanings of its words do not express. Hence, it is necessary to examine the phenomenon of brevity that wisdom poetry is characterized by on the one hand, and the phenomenon of expansion of meaning on the other hand, in addition to the artistic and creative value achieved from the use of these arts, which was a direct reason for the prevalence of this type of poetry among Arab societies across the ages, and the interaction of these societies with it.
Keywords: employment; rhetoric; wisdom poetry; recipient